Predicting Stock Returns in Indonesian Technology Companies - Ni Putu Mariyani; Putu Wenny Saitri; Ni Putu Yuria Mendra (AIBPM Publisher, 2025)
Stock return is one of the considerations for investors in making investment decisions because when investing in shares, investors prefer companies that can provide high returns. This research aims to test and analyze the influence of several variables, including the proportion of profit margin earnings before interest, taxes, and depreciation (EBITDM), current ratio (CR), debt-to-equity ratio (DER), total asset turnover (TATO), and price-to-book value (PBV) on stock return in the technology sector listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The population in this study consists of companies in the technology sector listed on the IDX during the 2021–2023 period. The sample selection in this study used the purposive sampling method, with observations of 39 technology sector companies, and employed multiple linear regression analysis techniques. The research results show that the variables CR, TATO, and PBV have a positive effect on stock return, while EBITDM and DER have no effect on stock return. For further research, it is recommended to include other independent variables, such as return on equity (ROE), net profit margin (NPM), and dividend yield (DY). Additionally, subsequent studies should consider expanding the sample scope and extending the observation period.